Biomedical application of responsive ‘smart’ electrospun nanofibers in drug delivery system: A minireview - Nurul Huda Kamsani; Muhammad Salahuddin Haris; Manisha Pandey; Muhammad Taher; Kamal Rullah (Arabian Journal of Chemistry, 2021)
Electrospinning is a versatile method for producing continuous nanofibers. It has since become an easy and cost-effective technique in the manufacturing process and drawn keen interests in most biomedical field applications. Nanofibers have garnered great attention in nanomedicine due to their resemblance with the extracellular matrix (ECM). Like nanoparticles, its unique characteristics of higher surface-to-volume ratio and the tunability of the polymers utilizing nanofiber have increased the efficiency in encapsulation and drug-loading capabilities. Smart or “stimuli-responsive” polymers have shown particular fascination in controlled release, where their ability to react to minor changes in the environment, such as temperature, pH, electric field, light, or magnetic field, distinguishes them as intelligent. Polymers are a popular material for the design of drug delivery carriers; consequently, various types of drugs, including antiviral, proteins, antibiotics, DNA and RNA, are successfully encapsulated in the pH-dependent nanofibers with smart polymers which is a polymer that can respond to change such as pH change, temperature. In this minireview, we discuss applications of smart electrospun pH-responsive nanofibers in the emerging biomedical developments which includes cancer drug targeting, oral controlled release, wound healing and vaginal drug delivery.